Methodological and Theoretical Approaches to the Study of Governance and Policy Transfer in Vocational Education and Training - Barabasch, Antje [Verfasser] (My University, 2010)
"This introductory article offers not only a synthesis of methodological approaches, methods, conceptual considerations and theoretical frameworks that are introduced in the various articles in this special issue, it also reaches beyond this collection in referring to interdisciplinary approaches to the study of vocational education and training (VET) governance. The latter are specifically intended to assist in analysing the role of the individual, political groups or networks in governing VET and potentially determining a VET policy transfer process. The author explains how the study of governance is directly connected to the study of policy transfer and specifically introduces categories derived from the behavioural science in order to substantiate the thesis that existing governance studies have not paid attention to the essential category of the human or social factor." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 4.3 Steuerung; Berufsbildungspolitik; Bildungssteuerung; Berufsbildungssystem; Transfer; Soziale Faktoren